A novel solar-powered electrochemical mineralization system for persistent remediation of uranium-contaminated groundwater. (September 2022) - Zhang, Yu; Li, Mi; Hua, Yilong; Wu, Xiaoyan; Zhang, Xiaowen; Fang, Qi; Cai, Tao
Abstract: Reduction of the migratory ability of uranium via reduction, co-precipitation or immobilization is a widely used technology for remediation of uranium contaminated groundwater (UCG). However, the re-released uranium due to environmental alterations such as oxidation, acid dissolution, or microbial decomposition limits the long-term effect of UCG remediation. Here, we developed a novel solar-powered electrochemical mineralization (SPEM) system for persistent remediation of UCG under laboratory conditions. The SPEM system incorporates uranium into magnetite crystal to achieve long-term stability of uranium. The effects of photoelectric conversion, subsurface void fraction, groundwater seepage velocity, and electrode configuration on uranium removal were systematically analyzed. The results showed that the remediation system had excellent adaptability to complex water quality and geological conditions, and could remediate large-area contamination. After 12 h of persistent treatment, the system with newly hexagonal two-dimensional electrode configuration (1A6C) reduced uranium concentration by more than 85% in simulated subsurface environment. The mineralized uranium was not re-released within continuous rinsing of treated regions using an acid solution (pH = 3.0), for 370 h. The developed method solely requires metallic iron as a raw material, which has high and long-term efficiency, is eco-friendly, simple, and widely applicable, thus reliable for the remediation of deep UCG. Graphical abstract: Image 1 Highlights: A SPEM system was constructed for persistent remediation of U from groundwater. Effects of illumination and hydrogeological conditions on U removal were clarified. The SPEM with a 1A6C electrode arrangement efficiently removed U from groundwater. U remains stable in remediated regions and is not re-released under acidic condition.